Prevalence of bimaxillary protrusion among UiTM orthodontic patients / Ruqoyyah Muslimat Othman ... [et al.] - Othman, Ruqoyyah Muslimat; Aidil Koay, Noor Airin; Abdul Ghani, Sarah Haniza; Norman, Noraina Hafizan (2019)
Objective: To determine the prevalence of bimaxillary protrusion in general and the prevalence of skeletal Class I and dental Class I bimaxillary protrusion/ proclination among orthodontic patients attending postgraduate orthodontic clinic at Faculty of Dentistry, Universiti Teknologi MARA (UiTM), Sungai Buloh, Malaysia. Materials and Methods: This is a cross sectional study which was carried out in two stages. The first part involves a random selection of 100 extra-oral profile photographs taken from postgraduate orthodontic residents' patient list. The photographs were taken using Canon digital SLR camera EOS 70D with macro lens EF 100mm (Canon Inc., Tokyo, Japan) with patients in natural head position. The photographs were visually analysed for its bimaxillary protrusion features by two operators. The second part comprises of analyses of extra-oral profile photographs as well as intra-oral photographs of right buccal segment view which was conducted in two separate sittings. In the first sitting, five assessors analysed 259 extra- and intra-oral photographs followed by 40 photographs assessed in the second sitting for skeletal and dental Class I bimaxillary protrusion/ proclination. Statistical analysis for Kappa score was performed to assess the agreement between assessors using SPSS version 23 and Stata version 13. Results: The first part of the study showed an average prevalence of 34% with bimaxillary protrusion in 100 orthodontic patients. Whilst in the second part, prevalence of skeletal and dental Class I bimax ranging from 28-33 per cent and 38-40 per cent respectively with very good and good inter-reliability agreement for both component. Conclusion: The prevalence of bimaxillary protrusion in general among UiTM orthodontic patients was found to range from 31 per cent to 37 per cent. Whilst the prevalence of skeletal and dental Class I bimax ranging from 28-33 per cent and 38-40 per cent respectively.